Atlas of Anatomy of the Peripheral Nerves : The Nerves of the Limbs - Student Edition - Rigoard, Philippe (Springer International Publishing : Imprint: Springer, 2017)
This innovative atlas focuses on peripheral nerves and provides a brand new approach compared to regular anatomy books. Using a modern 3D approach, it offers an alternative to conventional anatomical structures. It reviews all the anatomy and the morphology of these structures from an original point of view. In these three-dimensional diagrams, as well as in the watercolor drawings enhanced with a 3D inlay, each type of nerve is depicted in a minute detail. The atlas simplifies the anatomy and make it easy and understandable by allowing readers to develop a mental "real-time 3D GPS". The integration of MRI sections related to the drawings and the descriptions of the main nerve injuries provide medical students with a flexible but effective transition to the radiological interpretation and furthers the clinical learning process. After a detailed evaluation of the morphofunctional anatomy of the peripheral nerves, the authors present a collection of relevant data on neuromuscular transmission, both from classical and recent literature, ranging from the central and peripheral nervous system to the effector muscle. This information offers a basis for understanding the physiology, the pathology, and the repair prospects of peripheral nerves from a purely theoretical point of view. The book is divided into three main parts: - Fundamental notions: from immunohistochemistry to limb innervation - The upper limb: the brachial plexus and related peripheral nerves - The lower limb: the lumbosacral plexus and related peripheral nerves This atlas also features 261 outstanding full-colour 2D and 3D illustrations. Each picture has been designed in 2D and 3D with a combination of the original editor's personal drawings/paintings and 3D-modeling tools. This book is a valuable resource for anyone studying medicine, anaesthesiology, neurosurgery, spine surgery, pain, radiology or rheumatology and is also of high interest to the whole medical community in general.
Keywords: Medicine.; Human anatomy.; Anesthesiology.; Rheumatology.; Neurosurgery.; Orthopedics.; Minimally invasive surgery.; elektronické knihy; electronic books